Point Spectrum of Singularly Perturbed Self-Adjoint Operators - Konstantinov, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study the inverse spectral problem for the point spectrum of singularly perturbed self-adjoint operators.